Eutanasi inom smådjurssjukvården; yrkesverksamma djursjukskötares upplevelser - Brolin, Louise (2014)
The quality of health and care of our animals in the veterinary clinic is dependent on the veterinary nurse. Therefore it is important that the nurse has a good mental health and can provide this. Research shows that veterinarians are exposed to an elevated risk of suicide, moral stress, depression and anxiety. One of the factors contributing is believed to be exposure to euthanasia. The impact of euthanasia to veterinary nurses is yet unclear, as research focuses on veterinarians. The aim of this study was to explore veterinary nurses’ experiences during euthanasia and what factors negatively contributes to these experiences, if they had and wanted emotional support from their employer, weather or not they felt able to meet the owners´ feelings and if this ability had been provided to them through their education. The respondents were attained through a survey focusing on those who were profession active in the small animal veterinary practice.